Survival rates of oil-rehabilitated and non-rehabilitated little penguins after the C/V Rena oil spill, New Zealand. (September 2019) - Sievwright, Karin A.; Battley, Phil F.; McConnell, Helen; Armstrong, Doug P.; Morgan, Kerri J.
Abstract: We monitored the post-release survival of little penguins ( Eudyptula minor ) rehabilitated after the 2011 C / V Rena oil spill in New Zealand to assess the effectiveness of the rehabilitation process. Surveys were conducted over a 23-month period after the spill to assess whether survival differed between rehabilitated and control penguins. Survival probabilities from mark-recapture analyses were lower for both oiled and control penguins in the first six months of the study (monthly probability 0.92) but increased and remained high thereafter (monthly probabilities 0.97–1.0). Importantly, survival did not differ significantly between oiled and control birds throughout the study. Post-release survival of rehabilitated birds was not influenced by the degree of oiling, body mass (at admission or release), blood parameters (admission packed cell volume, total protein or blood glucose) or the duration of captivity. Rehabilitation therefore appeared to successfully reverse the negative effects of oiling on the post-release survival of treated penguins. Highlights: Post-release mass mortality of rehabilitated penguins was not observed. Post-release survival was similar between control and rehabilitated penguins. Oiling degree did not influence post-release survival of rehabilitated penguins. Body masses were similar between control and rehabilitated penguins. Post-release survival rates indicate successful rehabilitation of oiled penguins.